Effectiveness Of Core Stability Exercises In Improving Dynamic Sitting Balance In Post-Stroke Cases - Baliarsingh , Anuska; Ksirabdhi Tanaya(PT), Ashisha; Jahangir, SK.; Acharya , Ayaskanta; Ranjan Pattnaik, Soumya; Ambatkar , Manjusha (Journal of Neonatal Surgery, 2025)
Background: Dynamic sitting balance is a significant early indicator of mobility and independence after stroke, but trunk control is usually disturbed. Core stability exercises (CSEs) could be used to enhance postural control in this population. Objective: To determine the effectiveness of CSEs in improving dynamic sitting balance in adults after stroke. Methods: A randomized controlled trial in a tertiary center in Bhubaneswar involving 60 patients (45–75 years) who were randomized into CSE + routine physiotherapy (Group A) or routine physiotherapy alone (Group B). The most significant inclusion criteria were first-ever unilateral stroke in the past year, sitting ability ≥10 s, and baseline Trunk Impairment Scale (TIS) ≤10. Primary measures were TIS and an age-predicted sitting balance scale, both of which were measured at baseline and 3 months. Sessions were delivered 5 days/week for 45–60 minutes; CSEs targeted deep and global trunk stabilizers with increasing difficulty. Result: Both conditions exhibited important improvement in Trunk Impairment Scale (TIS) scores (p<0.001). The experimental condition improved from 7.37 ± 1.71 to 13.43 ± 2.06, while the control condition improved from 7.50 ± 1.94 to 12.10 ± 2.19. Between-group comparison revealed a significant difference in the experimental group's favor (t=4.303, p<0.001). The findings reveal that the experimental treatment induced greater improvement in sitting balance and trunk control compared to routine therapy. Conclusion: The integration of a systematic CSE program with routine physiotherapy results in clinically and statistically improved gains in post-stroke trunk control and dynamic sitting balance. CSEs are simple, low-cost, and can be integrated into routine rehabilitation procedures